Do mental skills make champions? Examining the discriminant function of the psychological characteristics of developing excellence questionnaire - Macnamara, A.; Collins, D. (Journal of Sports Sciences, 2013)
The ability to successfully develop to the highest levels in sport is dependent on a range of variables, not least an individual's ability to cope with the various challenges of development. Psychological Characteristics of Developing Excellence (PCDEs) include both the trait characteristics and the state-deployed skills that have been shown to play a crucial role in the realisation of potential. Psychological characteristics of developing excellence equip aspiring elites with the mental skills, attitudes, and emotions to cope with the challenges of the development pathway, as well as underpinning their capacity to make the most of their innate abilities. The Psychological Characteristics of Developing Excellence Questionnaire (PCDEQ) was designed to assess the possession and deployment of these characteristics. The purpose of this paper was to examine the ability of the Psychological Characteristics of Developing Excellence Questionnaire to effectively discriminate between good and poor developers based on their current possession and deployment of psychological characteristics of developing excellence. Two hundred and eighty-five athletes (n = 192 team athletes; n = 93 individual athletes) completed the Psychological Characteristics of Developing Excellence Questionnaire. Results from the discriminant function analysis suggest that the Psychological Characteristics of Developing Excellence Questionnaire correctly classifies between 67% and 75% of athletes based on their responses. The Psychological Characteristics of Developing Excellence Questionnaire can be used as a formative assessment tool to direct training programmes by identifying weaknesses in psychological characteristics of developing excellence and incorporating specific training to address these weaknesses in advance of developmental challenges.